Thallium-based high-temperature superconductors for beam impedance mitigation in the Future Circular Collider. (8th June 2017) - Calatroni, S; Bellingeri, E; Ferdeghini, C; Putti, M; Vaglio, R; Baumgartner, T; Eisterer, M
Abstract: CERN has recently started a design study for a possible next-generation high-energy hadron–hadron collider (Future Circular Collider—FCC-hh). The FCC-hh study calls for an unprecedented center-of-mass collision energy of 100 TeV, achievable by colliding counter-rotating proton beams with an energy of 50 TeV steered in a 100 km circumference tunnel by superconducting magnets which produce a dipole field of 16 T. The beams emit synchrotron radiation at high power levels, which, to optimize cryogenic efficiency, is absorbed by a beam-facing screen, coated with copper, and held at 50 K in the current design. The surface impedance of this screen has a strong impact on beam stability, and copper at 50 K allows for a limited beam stability margin only. This motivates the exploration of whether high-temperature superconductors (HTS), the only known materials possibly having a surface impedance lower than copper under the required operating conditions, would represent a viable alternative. This paper summarizes the FCC-hh requirements and focuses on identifying the best possible HTS material for this purpose. It reviews in particular the properties of Tl-based HTS, and discusses the consequent motivation for developing a deposition process for such compounds, which should be scalable to the size of the FCC components.